Partial safety factor design of rectangular partially prestressed concrete beams in ultimate flexural limit state - Agrawal, Gunjan; Bhattacharya, Baidurya (Journal of Structural Engineering, 2025)
Reliability-based structural design is necessary if uncertainties exist in loads, material and geometric properties and/or mathematical models. The partial safety factors (PSFs) used in reliability-based design, for a class of structural components under a given load combination and failure criteria, should preferably be applicable for a wide range of structural configurations and design options. This paper describes the methodology in detail for developing a set of optimal reliability-based PSFs for given limit state, load combination and target reliability. The class of structural components considered is rectangular partially prestressed concrete beams in ultimate flexure limit state subject to dead and live loads. The mechanical formulation of the flexural limit state is based on the principle behind prestressed concrete design recommended by IS 1343 and SP16. The first order reliability method (FORM) with Rackwitz-Fiessler transformation and gradient projection algorithm are used in this work and the methods are described in detail. Numerical examples involving flexural design of rectangular partially prestressed concrete beams are described. The conservatism in the code specified nominal moment capacity is brought out. A detailed survey of the statistics of related random variables is presented. The variation of the reliability index β as a function of the nominal load ratio, for different values of live load factor, characteristic compressive strength of concrete, nominal prestressing force, percentage reinforcement and eccentricity of the prestressing force, is determined. PSFs optimized for a range of load ratios and nominal prestressing force corresponding to a set of target reliabilities are presented.